A novel diphtheria toxin‐based bivalent human EGF fusion toxin for treatment of head and neck squamous cell carcinoma. Issue 4 (20th February 2021) - Qi, Zeng; Qiu, Yue; Wang, Zhaohui; Zhang, Huiping; Lu, Ling; Liu, Yanqiu; Mathes, David; Pomfret, Elizabeth A.; Gao, Dexiang; Lu, Shi‐Long; Wang, Zhirui
Abstract : Epidermal growth factor receptor (EGFR) is often overexpressed in head and neck squamous cell carcinoma (HNSCC) and represents a top candidate for targeted HNSCC therapy. However, the clinical effectiveness of current Food and Drug Administration (FDA)‐approved drugs targeting EGFR is moderate, and the overall survival rate for HNSCC patients remains low. Therefore, more effective treatments are urgently needed. In this study, we generated a novel diphtheria toxin‐based bivalent human epidermal growth factor fusion toxin (bi‐EGF‐IT) to treat EGFR‐expressing HNSCC. Bi‐EGF‐IT was tested for in vitro binding affinity, cytotoxicity, and specificity using 14 human EGFR‐expressing HNSCC cell lines and three human EGFR‐negative cancer cell lines. Bi‐EGF‐IT had increased binding affinity for EGFR‐expressing HNSCC compared with the monovalent version (mono‐EGF‐IT), and both versions specifically depleted EGFR‐positive HNSCC, but not EGFR‐negative cell lines, in vitro . Bi‐EGF‐IT exhibited a comparable potency to that of the FDA‐approved EGFR inhibitor, erlotinib, for inhibiting HNSCC tumor growth in vivo using both subcutaneous and orthotopic HNSCC xenograft mouse models. When tested in an experimental metastasis model, survival was significantly longer in the bi‐EGF‐IT treatment group than the erlotinib treatment group, with a significantly reduced number of metastases compared with mono‐EGF‐IT. In addition, in vivo off‐target toxicities were significantly reduced in the bi‐EGF‐IT treatment group compared with the mono‐EGF‐IT group. These results demonstrate that bi‐EGF‐IT is more effective and markedly less toxic at inhibiting primary HNSCC tumor growth and metastasis than mono‐EGF‐IT and erlotinib. Thus, the novel bi‐EGF‐IT is a promising drug candidate for further development. Abstract : In this study, we have developed a diphtheria toxin‐based bivalent human EGF fusion toxin for the treatment of HNSCC with significantly improved efficacy and markedly less in vivo off‐target toxicity compared with the monovalent human EGF fusion toxin. The bivalent human EGF fusion toxin is a promising novel drug candidate for the treatment of EGFR‐positive HNSCC.